2017
DOI: 10.1080/16549716.2017.1332259
|View full text |Cite
|
Sign up to set email alerts
|

Are mobile health applications useful for supporting shared decision making in diagnostic and treatment decisions?

Abstract: Mobile health (mHealth) applications intended to support shared decision making in diagnostic and treatment decisions are increasingly available. In this paper, we discuss some recent studies on mHealth applications with relevance to shared decision making. We discuss the potential advantages and disadvantages of using mHealth in shared decision making in various contexts, and suggest some directions for future research in this quickly expanding field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Examining the use of technology in physician-patient relationships further, other studies generally discussed the usefulness of health apps for physician-patient interaction, for example, in shared decisionmaking (36). Abbasgholizadeh et al (36) reported mixed results for technology-supported physicianpatient interactions; for example, better accessibility to data, improved e ciency for the physician, realtime connectivity, or remote decision-making on the one hand, but diminished quality of care through overuse of mHealth, increased health disparities due to lacking mHealth access, or lack of mHealth regulation, on the other hand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining the use of technology in physician-patient relationships further, other studies generally discussed the usefulness of health apps for physician-patient interaction, for example, in shared decisionmaking (36). Abbasgholizadeh et al (36) reported mixed results for technology-supported physicianpatient interactions; for example, better accessibility to data, improved e ciency for the physician, realtime connectivity, or remote decision-making on the one hand, but diminished quality of care through overuse of mHealth, increased health disparities due to lacking mHealth access, or lack of mHealth regulation, on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to these authors, the higher workload for physicians can also affect the relationship negatively. Abbasgholizadeh, Menear, Robitaille, and Legare (36) reported that health apps have potential for improved patient participation in shared health decision-making, but bear risks like security concerns or increased patient anxiety.…”
Section: Social Support and Technology-supported Diabetes Self-managementioning
confidence: 99%
“…Examining the use of technology in physician-patient relationships, other studies generally discussed the usefulness of health apps for physician-patient interaction, for example, the usefulness of health apps for shared decision-making (46). Abbasgholizadeh et al (46) reported both positive and negative reasons for technology-supported physician-patient interactions, for example better accessibility to data, improved efficiency for the physician, real-time connectivity, or remote decision-making on the one hand, but diminished quality of care through overuse of mHealth, increased health disparities due to lacking mHealth access, or lack of mHealth regulation, on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to them the higher workload for physicians can also affect the relationship negatively. Abbasgholizadeh, Menear, Robitaille, and Legare (46) reported that health apps have potential for improved patient participation in shared health decision-making, but also bear risks like security concerns or increased patient anxiety.…”
Section: Relevance Of Social Support For (Technology-supported) Diabementioning
confidence: 99%
“…Furthermore, acceptance of health technology may also be related to a participants' understanding of their condition and their overall interest in their own health or health literacy; in a recent systematic review of the effect of telehealth tools on vulnerable populations, health literacy was only assessed in one of the included 18 studies [33]. Finally, there is a need for further research in remote consultations to consider the impact on other outcomes beyond healthcare use, and patient satisfaction to patient behaviours (such as drug adherence) and shared decision-making [34].…”
mentioning
confidence: 99%